2018
DOI: 10.1039/c7py02137b
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of ultrastable, biopassive and lubricious cyclic poly(2-alkyl-2-oxazoline) brushes

Abstract: Bilayer films featuring cyclic, poly(2-alkyl-2-oxazoline) brush interfaces display excellent biopassivity, lubrication and long-term stability in chemically harsh aqueous environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 71 publications
1
56
0
Order By: Relevance
“…The improved non‐cell adhesive properties of the BOB could be attributed to molecular design: in a study on polyethyloxazoline brushes, which were grafted to a surface in either a loop or as linear grafts, it was shown that a loop can indeed be more efficient in resisting biofouling than linear chains . This finding can be attributed to the ability of hydrophilic loops to form significantly more hydrated brushes . The importance of hydration has previously also been shown for OEG‐based self‐assembled monolayers, where the protein repelling properties depend on the conformation of the OEG chains and the resulting hydration of the monolayer …”
Section: Antifouling Properties Of Electrospun Scaffoldsmentioning
confidence: 91%
“…The improved non‐cell adhesive properties of the BOB could be attributed to molecular design: in a study on polyethyloxazoline brushes, which were grafted to a surface in either a loop or as linear grafts, it was shown that a loop can indeed be more efficient in resisting biofouling than linear chains . This finding can be attributed to the ability of hydrophilic loops to form significantly more hydrated brushes . The importance of hydration has previously also been shown for OEG‐based self‐assembled monolayers, where the protein repelling properties depend on the conformation of the OEG chains and the resulting hydration of the monolayer …”
Section: Antifouling Properties Of Electrospun Scaffoldsmentioning
confidence: 91%
“…Recently, both linear and cyclic variants of poly(2‐oxazoline) were studied by Morgese et al . which also showed long‐term stability for poly(2‐oxazoline)s, both in terms of biopassivity to nonspecific adsorption and lubrication properties . On the contrary, Ulbricht et al .…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, the slope of the F f L profiles progressively decreased with the glass-transition temperature (T g ) of the polymer, which was 78, 16, and À 35°C for PMOXA, [64] PMOZI, [65] and PEG, [66] respectively, demon-…”
Section: Alternatives To Peg Brushesmentioning
confidence: 99%